A protocol for efficient callus induction from hypocotyls explant in chickpea (Cicer arietinum) - PRABHAT KUMAR; M S SANGWAN; NARESH MEHTA (The Indian Journal of Agricultural Sciences, 2014)
Callus induction in any crop is a pre-requisite for its utilization in tissue culture based techniques like somaclonal variation, screening of calli against biotic or abiotic stress, regeneration of plant and transgenic plant development. In present investigation an attempt was made to develop a protocol for efficient callus induction from hypocotyl explants in chickpea crop. Among different combinations of growth regulators- auxin alone and in combination with cytokinin used for callus induction, MS basal medium supplemented with IAA (2.5 mg/L) + BAP (0.5 mg/L), 2, 4-D (2 mg/L) and NAA (3 mg/L) + BAP (3 mg/L) were induced significantly higher callus induction (100%) in all genotypes of chickpea E100 Y (M), Gaurav and Pb-7) and (L-550) from hypocotyls explant.